The Alteration of T-Cell Heterogeneity and PD-L1 Colocalization During dMMR Colorectal Cancer Progression Defined by Multiplex Immunohistochemistry - Yan, Hongkai; Li, Yaqi; Wang, Xiaoyu; Qian, Juanjuan; Xu, Midie; Peng, Junjie; Huang, Dan (Frontiers in Oncology, 2022)
Background: Immune checkpoint inhibitors (ICIs) are quickly becoming key instruments in the treatment of mismatch repair-deficient (dMMR) colorectal cancers (CRCs). Despite their clinical success, ICIs have several limitations regarding their use. Only approximately 15% of all CRCs have dMMR status, and the overall response rate of ICIs is around 40%. The mechanism of ICI resistance is not clear, and this study is limited by the lack of information on characterization of immune microenvironment during the progression from early- to advanced-stage dMMR CRC. Methods: We used multiplex immunohistochemistry (mIHC) with two panels, each containing five markers, to simultaneously analyze the proportions of immune microenvironment constituents in 59 advanced-stage dMMR CRC patients and 24 early-stage dMMR CRC patients. We detected immune cell-associated signatures in the epithelial and stromal regions and statistically evaluated the predictive value of these immune molecules. A t-test, Mann–Whitney U test, Cox proportional hazards regression model, univariate Cox models, and Kaplan–Meier method were used to analyze immune cell proportions and survival data. Results: We observed significantly higher proportions of CD8+ cytotoxic T cells (CD8+) (p = 0.001), CD8+ memory T cells (CD8+CD45RO+) (p = 0.032), and CD4+ regulatory T cells (CD4+FOXP3+) (p = 0.011) in the advanced-stage dMMR CRCs than in the early-stage dMMR CRCs. Furthermore, CD3+ T cells with PD-L1 colocalization (CD3+PD-L1+) (p = 0.043) and CD8+ T cells with PD-L1 colocalization (CD8+PD-L1+) (p = 0.005) were consistently more numerous in patients in the advanced stage than in the early stage. Our analyses revealed that a high proportion of CD3+PD-1+ T cells was an independent prognostic factor of overall survival (OS) (hazard ratios (HR) = 9.6, p < 0.001) and disease-free survival (DFS) (HR = 3.7, p = 0.010) in advanced-stage patients. Conclusion: High numbers of CD8+ cytotoxic T cells, and CD8+ memory T cells, which usually represent cytotoxic function of adaptive immune system, and possibly enhanced inhibition factors, like CD4+ regulatory T cells, and PD-L1 colocalized T cells were associated with the transformation of the immune microenvironment from early stage to advanced stage in dMMR CRCs. Furthermore, CD3+PD-1+ T cells are a prognostic factor for dMMR patients.